A Study of Bus High-Resolution GPS Speed Data Accuracy. Issue 8 (December 2018) - Figliozzi, Miguel A.; Stoll, Nicholas B.
The recent availability of high-frequency transit (HFT) GPS data for buses has allowed the estimation of detailed bus-travel speed profiles between bus stops. HFT data are defined as data comprising GPS vehicle trajectory recorded at or less than 5 s intervals. With HFT data it is now possible to measure changes in bus speed at specific locations of interest, such as intersections, ramps, crosswalks, and so on. Previous research efforts have not compared GPS-based bus speeds with general traffic speeds at specific locations between stops. This research fills this knowledge gap, utilizing accurate stationary radar speed data as a baseline or ground truth data to estimate GPS-based bus speed accuracy. A thorough data analysis of the bus and traffic speed data indicates that HFT speed estimations between stops are accurate and highly correlated with traffic speeds. Time–space speed profiles and regression analysis are utilized to quantify factors that affect HFT speed estimation accuracy. The relative advantages and limitations of the HFT data are presented and discussed. This study concludes that large HFT datasets can be utilized to accurately monitor speeds between transit stops. HFT datasets are suitable to cost-effectively monitor recurrent arterial speed performance for both passenger and transit vehicles.